Krisis Legitimasi Regulasi dalam Perlindungan Hak Digital pada Era Ekonomi Data dan Pengawasan Teknologi - Fajar Aditya Pranowo; Galih Putra Wiratama (Perkara : Jurnal Ilmu Hukum dan Politik, 2026)
The rapid expansion of the digital economy and surveillance technologies has raised critical concerns regarding the legitimacy of regulatory frameworks in protecting digital rights. The increasing reliance on data-driven economy models has transformed personal data into a strategic asset, intensifying power imbalances between governments, corporations, and individuals. This study aims to analyze the legitimacy crisis in digital rights regulation by identifying key influencing factors and evaluating governance models to address these challenges. The research employs a normative juridical approach, utilizing secondary data from legal documents, policy reports, and prior scholarly studies, and analyzing them through a qualitative-descriptive framework. The findings reveal that approximately 68% of regulatory challenges are associated with issues of over-surveillance and lack of transparency, while 54% are linked to regulatory lag in adapting to technological advancements. Additionally, around 61% of analyzed cases indicate significant asymmetry in power relations between stakeholders. The study also finds that the hybrid governance model demonstrates higher adaptability, with an effectiveness rate reaching 72% compared to centralized (58%) and decentralized (63%) approaches. These results indicate that digital surveillance practices, including AI profiling and mass surveillance, significantly undermine public trust in regulatory systems. This study contributes by proposing an integrated framework of regulatory legitimacy that emphasizes legality, accountability, transparency, and effectiveness, while highlighting the importance of adaptive and participatory regulatory approaches to ensure balanced protection of digital rights in the evolving digital ecosystem